Computed tomography aortic valve calcium scoring for the assessment of aortic stenosis progression. Issue 24 (5th October 2020) - Doris, Mhairi Katrina; Jenkins, William; Robson, Philip; Pawade, Tania; Andrews, Jack Patrick; Bing, Rong; Cartlidge, Timothy; Shah, Anoop; Pickering, Alice; Williams, Michelle Claire; Fayad, Zahi A; White, Audrey; et al.
Abstract : Objective: CT quantification of aortic valve calcification (CT-AVC) is useful in the assessment of aortic stenosis severity. Our objective was to assess its ability to track aortic stenosis progression compared with echocardiography. Methods: Subjects were recruited in two cohorts: (1) a reproducibility cohort where patients underwent repeat CT-AVC or echocardiography within 4 weeks and (2) a disease progression cohort where patients underwent annual CT-AVC and/or echocardiography. Cohen's d-statistic ( d ) was computed from the ratio of annualised progression and measurement repeatability and used to estimate group sizes required to detect annualised changes in CT-AVC and echocardiography. Results: A total of 33 (age 71±8) and 81 participants (age 72±8) were recruited to the reproducibility and progression cohorts, respectively. Ten CT scans (16%) were excluded from the progression cohort due to non-diagnostic image quality. Scan-rescan reproducibility was excellent for CT-AVC (limits of agreement −12% to 10 %, intraclass correlation (ICC) 0.99), peak velocity (−7% to +17%; ICC 0.92) mean gradient (−25% to 27%, ICC 0.96) and dimensionless index (−11% to +15%; ICC 0.98). Repeat measurements of aortic valve area (AVA) were less reliable (−44% to +28%, ICC 0.85). CT-AVC progressed by 152 (65–375) AU/year. For echocardiography, the median annual change in peak velocity was 0.1 (0.0–0.3) m/s/year, mean gradient 2 (0–4) mm Hg/year and AVA −0.1 (−0.2–0.0) cm 2 /year. Cohen's d-statistic was more than double for CT-AVC ( d =3.12) than each echocardiographic measure (peak velocity d =0.71 ; mean gradient d =0.66; AVA d =0.59, dimensionless index d =1.41). Conclusion: CT-AVC is reproducible and demonstrates larger increases over time normalised to measurement repeatability compared with echocardiographic measures.